The Effect of Influencer Marketing on Consumer Engagement and Brand Loy-alty - Yong, Sean Calvin Shin Ching; Gao, Xing; Poh, Wen Sern (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Companies spend their social media advertising on several platforms, including Facebook, Instagram, TikTok, and Xiaohongshu. The proliferation of technology and the increasing accessibility for individuals to establish careers on social media platforms have led to the emergence of influencer marketing as a strategy that can foster consumer engagement within these platforms and perhaps impact brand loyalty. This study examines the effect of influencers marketing approach in the Malaysian context, taking into consideration the growing prominence of this phenomenon. This study utilized descriptive analysis to offer generalizable recommendations for companies regarding the effect of adopting the influencer marketing approach as a strategic method. The findings of this study provide valuable insights for companies seeking to develop their marketing strategies and promote consumer engagement to expand their market position.